Advances in the Safe Disposal and Comprehensive Utilization of Spent Carbon Anode From Aluminum Electrolysis: Prospects for Extraction and Application of Carbon Resources From Hazardous Waste - Li, Bin; Zhou, Jun; Yao, Zhen; Peng, Qian; Liu, Mengnan; Li, Xiaoqing; Liu, Wei (Frontiers in Energy Research, 2021)
Spent carbon anode (SCA) is a dangerous solid waste that is continuously discharged from the aluminum electrolysis industry and has a large number of valuable resources and a high risk of environmental pollution. Its safe disposal and resource utilization have become a resource and environmental problem that must be solved urgently. Current methods for SCA disposal include flotation, vacuum metallurgy, physical activation, roasting, bubbling fluidized bed combustion, alkali fusion, alkali leaching, and chemical leaching combined with high temperature graphitization. In this paper, the material composition, resource properties, and environmental risks of SCA are discussed. Working principle, treatment process, advantages and disadvantages of the above methods are also briefly described and compared. Results showed that flotation is the safest disposal and comprehensive utilization technology that is suitable for characteristics of SCA raw materials and has the most large-scale application potential. In addition, characteristics of SCA recovery products are correlated to the recycling of aluminum reduction cells. This technology can alleviate the shortage of high-quality petroleum coke resources in China's carbon material industry and the high cost of raw materials in aluminum electrolysis industry.